Simulated spectra (IR and Raman), NLO, AIM and molecular docking of carisoprodol from DFT approach - Chaudhary, Manoj Kumar; Chaudhary, Tarun; Joshi, Bhawani Datt (BIBECHANA, 2021)
The aim of this study to explore the spectroscopic behavior of carisoprodol in terms of simulated spectra (IR and Raman). The intramolecular H-bond of the molecule has been inspected from the Atoms in a Molecule (AIM) approach which infers that there exists partial covalent H-bond in nature. The protein-ligand binding activity of the drug molecule has been analyzed theoretically from the molecular docking approach with the predicted targets in terms of binding energy and conventional H-bond with residue. The molecular docking analysis of the title molecule explores that the binding energy with the protein acetylcholinesterase is more than the protein epoxide hydrolase1. The nonlinear optical (NLO) behavior of the title molecule has been scrutinized which motivates that the potent use of the molecule as NLO material.BIBECHANA 18 (1) (2021) 48-57